Upside Down Crossed Cerebellar Diaschisis: Proposing Chronic Stimulation of the Dentatothalamocortical Pathway for Post-Stroke Motor Recovery - Machado, Andre; Baker, Kenneth B. (Frontiers in Integrative Neuroscience, 2012)
Background: Stroke remains the leading cause for long-term motor impairment in the industrialized world. New techniques are needed to improve outcomes. Objective: To propose chronic electrical stimulation of the dentatothalamocortical pathway as a method for enhancing cortical excitability and improving motor recovery following stroke. Method: In previous studies, motor evoked potentials (MEP) were derived from intracortical microstimulation (ICMS) and used to index cortical excitability in rats undergoing continuous, asynchronous deep cerebellar stimulation. In a separate set of experiments, the effect of chronic deep cerebellar stimulation on motor recovery was tested in rats following large ischemic strokes. Results: Deep cerebellar stimulation modulated cortical excitability in a frequency dependent fashion. Beta band stimulation yielded sustained increment in excitability and was associated with enhanced motor recovery compared to sham stimulation. Conclusion: Chronic deep cerebellar stimulation enhances recovery of motor function following large ischemic strokes in the rat. The effect can be attributed to increased cortical excitability. Given that deep brain stimulation is already a well established method, this new approach to motor recovery may be a viable option for human translation in stroke rehabilitation.